KONTRIBUSI PENDAPATAN TENAGA KERJA WANITA PADA USAHA EMPING MELINJO TERHADAP PENDAPATAN KELUARGA DI DESA PLUMBON KECAMATAN LIMPUNG KABUPATEN BATANG - Miratus Saadah; Sri Wahyuningsih; Shofia Nur Awami; Lutfi Aris Sasongko (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2021)
The purpose of this research is to find out 1)the reasons why women workers work in melinjo chips, 2)the average allocation of women's work hours in melinjo chips, 3)the contribution of women workers to melinjo chips businesses on family income and, 4)factors that influence women's income contribution to the melinjo chips business. Respondents were taken by purposive sampling with the number of respondents as many as 45 women workers in 3 business ventures in Plumbon Village, Limpung District, Batang Regency. The results showed that the reason of women work in the business seen from dominant economic factors to help husbands find additional household income. While social factors, namely to fill spare time. The average working hours of women workers in melinjo business is 8 hours/day. The contribution of women workers in the emping melinjo business to family income was 33,68 percent. R2 value obtained using multiple linear regression models of 0.686 shows that the proportion of the influence of independent variables (women's income, husband's income and the number of family dependents) on the dependent variable in the form of women's income contribution to the melinjo chips business was 68.6% while the remaining 31.4% is influenced by other variables not found in the linear regression model in this study. The results of the F-test and t-test showed that the variance in women's income, husband's income and the number of family dependents had a significant effect on women's income contribution.